Knowledge attitude and practice on prevention of hepatitis B infection among medical students of a tertiary care centre in Tamil Nadu, India - M. C., Vasantha Mallika; S., Sivaanusuya (International Journal of Research in Medical Sciences, 2020)
Background: Hepatitis B infection is a serious global public health problem. About two billion people are infected with hepatitis B Virus (HBV) all over the world. The prevalence of HBV infection in India is 4%(2%-8%) with more prevalence among health care workers. Medical students represent a group that is at high-risk for acquiring and spreading hepatitis B infection. Despite increasing prevalence of HBV infection, there is paucity of knowledge, attitude and practice on HBV among medical students. Objective of the study was to assess the knowledge, attitude and practices on prevention of hepatitis B infection among medical students of Sree Mookambika Institute of Medical Sciences, Kulasekharam. Methods: A cross sectional study was conducted among 205 MBBS students using a pretested self-administered questionnaire for assessing the knowledge, attitude, and practice on prevention of HBV infection after obtaining informed consent from the participants. Results: Among 205 MBBS students, correct response towards Knowledge, Attitude, and Practices were given by 77.07%, 77.56%, and 76.59% respectively, 79.5% of the students were fully vaccinated; 20.5% were partially vaccinated against Hepatitis B Virus infection. Conclusions: The medical students are at a very high risk of contracting HBV infection during their training period in view of low HBV vaccine uptake rate and high chance of accidental exposure to blood infected with HBV. Creating awareness among medical students on various aspects of Hepatitis B infection through health education programs before their exposure in medical colleges and subjecting them to active immunization against HBV are mandatory to control the spread of Hepatitis B viral infection.